Habitat and Predator Influences on the Spatial Ecology of Nine-Banded Armadillos - Robert C. Lonsinger; Ben P. Murley; Daniel T. McDonald; Christine E. Fallon; Kara M. White (Diversity)
Mesopredator suppression has implications for community structure, biodiversity, and ecosystem function, but mesopredators with physical defenses may not avoid apex predators. We investigated nine-banded armadillos (Dasypus novemcinctus) in southwestern Oklahoma (USA) to evaluate if a species with physical defenses was influenced by a dominant predator, the coyote (Canis latrans). We sampled nine-banded armadillos and coyotes with motion-activated cameras. We used single-species and conditional two-species occupancy models to assess the influences of environmental factors and coyotes on nine-banded armadillo occurrence and site-use intensity (i.e., detection). We used camera-based detections to characterize the diel activity of each species and their overlap. Nine-banded armadillo occupancy was greater at sites closer to cover, with lower slopes, and further from water, whereas coyote space use was greater at higher elevations; both species were positively associated with recent burns. Nine-banded armadillo occurrence was not influenced by coyotes, but site-use intensity was suppressed by the presence of coyotes. Nine-banded armadillos (strictly nocturnal) and coyotes (predominantly nocturnal) had a high overlap in summer diel activity. Nine-banded armadillos are ecosystem engineers but are often considered a threat to species of concern and/or a nuisance. Thus, understanding the role of interspecific interactions on nine-banded armadillos has important implications for conservation and management.